2011
DOI: 10.1007/s00064-010-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the comminuted radial head fracture by a bipolar radial head prosthesis

Abstract: A total of 13 patients with 15 radial head prosthesis were analyzed at a mean follow-up of 29.5±20.8 months. In all patients, the elbow was stable. Subjectively, good and excellent results were found with one exception. Compared to the pretrauma status, the subjective rate was 78±12%. Based on the Radin and Riseborough score, 6 of the results were good and 9 were fair. According to the Broberg and Morrey score, 1 result was very good, 8 were good, and 6 were fair. The mean DASH score was 9.9±9.7 points. Two te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The relationship between the trial implant and intra-operative anatomical landmarks may also help in identifying the correct Rh size. Doornberg et al [ 13 ] found on CT reconstruction that the lateral edge of the coronoid articular surface is a reproducible landmark, and suggested to place the articular surface of the implant slightly more proximal than this landmark, whereas Müller et al [ 40 ] used trial stems to determine the size of the implant and concluded recommending to obtain 0.5 mm between the head of the replacement and the capitulum humeri. The lesser sigmoid notch of the ulna, which has been demonstrated to be a reproducible landmark to choose the implant height [ 41 ], has also been proposed as a possible landmark to assist in choosing the correct Rh diameter, but has been associated to poor interobserver reliability both intra-operatively and on preoperative CT scans [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the trial implant and intra-operative anatomical landmarks may also help in identifying the correct Rh size. Doornberg et al [ 13 ] found on CT reconstruction that the lateral edge of the coronoid articular surface is a reproducible landmark, and suggested to place the articular surface of the implant slightly more proximal than this landmark, whereas Müller et al [ 40 ] used trial stems to determine the size of the implant and concluded recommending to obtain 0.5 mm between the head of the replacement and the capitulum humeri. The lesser sigmoid notch of the ulna, which has been demonstrated to be a reproducible landmark to choose the implant height [ 41 ], has also been proposed as a possible landmark to assist in choosing the correct Rh diameter, but has been associated to poor interobserver reliability both intra-operatively and on preoperative CT scans [ 20 ].…”
Section: Discussionmentioning
confidence: 99%